The BiP cochaperone ERdj4 is required for B cell development and function. - Jill M Fritz; Timothy E Weaver (PLoS ONE, 2014)
ERdj4 is a BiP cochaperone regulated by the unfolded protein response to facilitate degradation of unfolded and/or misfolded proteins in the endoplasmic reticulum. As the unfolded protein response plays a critical role in B cell maturation and antibody production, ERdj4 gene trap mice were generated to determine if this chaperone was required for B cell homeostasis. Homozygosity for the trapped allele resulted in hypomorphic expression of ERdj4 in bone marrow cells and abnormal development of hematopoietic lineages in the bone marrow. The number of myeloid cells was increased, while the number of erythroid and B lymphoid cells was reduced in ERdj4 gene trap mice compared to controls. An intrinsic B cell defect was identified that decreased survival of B cell precursors including large and small pre-B, and immature B cells. Consistent with impaired B lymphopoiesis, the number of mature follicular B cells was reduced in both the bone marrow and spleen of ERdj4 gene trap mice. Paradoxically, unchallenged ERdj4 gene trap mice showed non-specific hypergammaglobulinemia and gene trap B cells exhibited increased proliferation, survival and isotype switching in response to LPS stimulation. Although ERdj4 gene trap mice responded normally to T cell-independent antigen, they failed to mount a specific antibody response to T cell-dependent antigen in vivo. Collectively, these findings demonstrate that the chaperone activity of ERdj4 is required for survival of B cell progenitors and normal antibody production.